Differential Reorganization of SMA Subregions After Stroke: A Subregional Level Resting-State Functional Connectivity Study - Liu, Huaigui; Cai, Wangli; Xu, Lixue; Li, Wei; Qin, Wen (Frontiers in Human Neuroscience, 2020)
Background and Purpose— The human supplementary motor area (SMA) contains two functional subregions of the SMA proper and preSMA, however, the reorganization patterns of the two SMA subregions after stroke remain uncertain. Meanwhile, a focal subcortical lesion may affect the overall functional reorganization of brain networks. We sought to identify the differential reorganization of the SMA subregions after subcortical stroke using the resting-state functional connectivity (rsFC) analysis. Methods—Resting-state functional MRI was conducted in 25 patients with chronic capsular stroke exhibiting well-recovered global motor function (Fugl-Meyer score > 90). The SMA proper and preSMA were identified by the rsFC-based parcellation and the rsFCs of each SMA subregion were compared between stroke patients and healthy controls. Results—Despite of common rsFC with the fronto-insular cortex (FIC), the SMA proper and preSMA were mainly correlated with the sensorimotor areas and cognitive-related regions, respectively. In stroke patients, the SMA proper and preSMA exhibited completely different functional reorganization patterns: the former showed increased rsFCs with the primary sensorimotor area and caudal cingulate motor area (CMA) of the motor execution network, whereas the latter showed increased rsFC with the rostral CMA of the motor control network. Both of the two SMA subregions showed decreased rsFC with the FIC in stroke patients; the preSMA additionally showed decreased rsFC with the prefrontal cortex. Conclusion—Although both SMA subregions exhibit functional disconnection with the cognitive-related areas, the SMA proper is implicated in the functional reorganization within the motor execution network, whereas the preSMA is involved in the functional reorganization within the motor control network in stroke patients.